The infrastructural role of education in the social and investment model of economic growth: the specifics of emerging markets - Semenova, Galina N.; Krupnov, Yuriy A.; Kostyukova, Elena I.; Satsuk, Tatiana P. (Frontiers in Education, 2023)
The purpose of this paper is to determine the directions and to specify the infrastructural role of higher education in the social and investment model of economic growth in view of the specifics and perspectives of emerging economies. Correlation analysis is used to determine the dependence between the directions of higher education’s development and the target results of its contribution to the implementation of the social and investment model of economic growth in emerging economies. These connections are specified with the help of regression analysis. Then, the simplex method is used to determine target landmarks for the selected directions. According to the experience of the top emerging economies with the highest level of economic innovative development in 2020, maximization (up to 100%) of knowledge-intensive employment (+299.29%), medium-tech and hi-tech manufacturing (+223.42%) and e-participation (+19.98%) requires the increase in the number of students per 1 lecturer in higher education by 387.26%, growth of mobility in higher education by 1,116.27%, and increase in QS university ranking by 139.13%. It is proved that only three directions of higher education’s development are significant and have to be implemented to support social and investment model of economic growth in emerging economies: increase in the number of students per 1 lecturer in higher education, growth of mobility in higher education, and increase in QS university ranking.